The Mediterranean Genetic Code - Grapevine and Olive 2013
DOI: 10.5772/51976
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Local Grapevine Germplasm: Exploitation of Natural Defence Mechanisms to Biotic Stresses

Abstract: The relationships between plant and pathogen start with the initial contact phase between infective propagules and the plant tissue surfaces. As response plants are able to activate defence mechanisms that may be referred to constitutive or inducible defences. 2.1. Constitutive defences Constitutive defences are active in the plant before pathogen challenge. They are considered able to limit the entry phase of parasite in host tissues through direct penetration or pre-existing tissues opening and to contrast t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 108 publications
(127 reference statements)
0
6
0
Order By: Relevance
“…The duration of the latent period indicates the time required for the pathogen to produce sporangia on the lesion surface. A longer latent period may result from reduced hyphal growth in the mesophyll of the host plant due to the thickness of the spongy mesophyll and cell walls 4,22,62 . A longer latent period may also result from a reduced number or functioning of haustoria resulting from HR 14 , such that the flow of nutrients from host cells to the intercellular mycelium is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of the latent period indicates the time required for the pathogen to produce sporangia on the lesion surface. A longer latent period may result from reduced hyphal growth in the mesophyll of the host plant due to the thickness of the spongy mesophyll and cell walls 4,22,62 . A longer latent period may also result from a reduced number or functioning of haustoria resulting from HR 14 , such that the flow of nutrients from host cells to the intercellular mycelium is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…sylvestris, a wild species indigenous to Transcaucasia (Olmo 1976) and the Mediterranean region (Arroyo-García et al 2006, Grassi et al 2003. During the 19th century, several grape pathogens, notably DM and powdery mildew, were introduced from North America into Europe, where those pathogens caused serious losses in V. vinifera production (Muganu & Paolocci 2013, Reisch et al 2012. Many crosses between V. vinifera and wild species have been made to develop disease-resistant cultivars (Eibach & Töpfer 2014, Reisch & Pratt 1996.…”
Section: Grapevine Downy Mildewmentioning
confidence: 99%
“…We observed that stomata dimension and density are influenced by polyploidization, being larger in size and less numerous in tetraploids. This characteristic can affect infections, as stomata are one of the major portals for pathogen penetration [76]. Studies carried out on several grapevine varieties reported a positive correlation between susceptibility to downy mildew and stomatal density [75].…”
Section: Discussionmentioning
confidence: 99%